2012
DOI: 10.1590/s1806-37132012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Análise e validação de modelos probabilísticos de malignidade de nódulo pulmonar solitário em uma população no Brasil

Abstract: Advanced age, greater maximum SPN diameter, and spiculated margins were significantly associated with the diagnosis of SPN malignancy. Our analysis shows that, although both mathematical models were effective in determining SPN malignancy in our population, the 1997 model was superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In the earliest studies, the Mayo Clinic model was examined alone or in comparison to other models in small, unscreened populations, nearly all of patients undergoing resection for lung nodules (malignancy prevalence: 44–84%) [6468]. The Mayo Clinic model exhibited good discrimination in all studies except one [67] (AUCs, 0.67–0.80) and performed better than the VA model (0.68–0.73) [65, 66, 68], yet similar to the PKUPH model (0.81) [68]. However, calibration results, when reported, suggested that the Mayo Clinic model underestimated while the VA model overestimated the actual probability of malignancy [64, 66].…”
Section: Predicting Nodule Malignancy At Initial Detectionmentioning
confidence: 99%
“…In the earliest studies, the Mayo Clinic model was examined alone or in comparison to other models in small, unscreened populations, nearly all of patients undergoing resection for lung nodules (malignancy prevalence: 44–84%) [6468]. The Mayo Clinic model exhibited good discrimination in all studies except one [67] (AUCs, 0.67–0.80) and performed better than the VA model (0.68–0.73) [65, 66, 68], yet similar to the PKUPH model (0.81) [68]. However, calibration results, when reported, suggested that the Mayo Clinic model underestimated while the VA model overestimated the actual probability of malignancy [64, 66].…”
Section: Predicting Nodule Malignancy At Initial Detectionmentioning
confidence: 99%
“…We read with great interest the well-written manuscript by Melo et al,( 1 ) who analyzed clinical and radiological findings that influence the pathological diagnosis of solitary pulmonary nodule (SPN). They concluded that advanced age, greater maximum SPN diameter, and spiculated margins were significantly associated with the diagnosis of malignancy.…”
Section: To the Editormentioning
confidence: 99%
“…Lemos com grande interesse o bem elaborado artigo de Melo et al,( 1 ) que analisaram os achados clínicos e radiológicos que influenciam o diagnóstico patológico de nódulo pulmonar solitário (NPS). Concluíram que idade elevada, maior diâmetro do NPS e presença de margens espiculadas tiveram associações significativas com o diagnóstico de malignidade.…”
Section: Ao Editorunclassified
“…The etiological diagnosis of pulmonary nodules remains a challenge. Imaging tests are important for diagnostic suspicion and risk estimation, but biopsy is necessary to confirm malignancy [Melo 2012, Snoeckx 2017]. There are protocols and algorithms to estimate the probability of malignancy of lung nodules, and the American College of Chest Physicians (ACCP) guidelines suggest performing biopsies when this probability is above 60% [Dale 2012, Ito 2018, Swensen 1997…”
mentioning
confidence: 99%